Strong σ‐Hole Activation on Icosahedral Carborane Derivatives for a Directional Halide Recognition. Issue 1 (29th October 2020) - Beau, Maxime; Lee, Sunhee; Kim, Sooyeon; Han, Won‐Sik; Jeannin, Olivier; Fourmigué, Marc; Aubert, Emmanuel; Espinosa, Enrique; Jeon, Ie‐Rang
Abstract: Crystal engineering based on σ ‐hole interactions is an emerging approach for realization of new materials with higher complexity. Neutral inorganic clusters derived from 1, 2‐dicarba‐ closo ‐dodecaborane, substituted with ‐SeMe, ‐TeMe, and ‐I moieties on both skeletal carbon vertices are experimentally demonstrated herein as outstanding chalcogen‐ and halogen‐bond donors. In particular, these new molecules strongly interact with halide anions in the solid‐state. The halide ions are coordinated by one or two donor groups (μ1 ‐ and μ2 ‐coordinations), to stabilize a discrete monomer or dimer motifs to 1D supramolecular zig‐zag chains. Crucially, the observed chalcogen bond and halogen bond interactions feature remarkably short distances and high directionality. Electrostatic potential calculations further demonstrate the efficiency of the carborane derivatives, with V s, max being similar or even superior to that of reference organic halogen‐bond donors, such as iodopentafluorobenzene. Abstract : Substituted carboranes with ‐SeMe, ‐TeMe, and ‐I groups on the skeletal carbon vertices are shown to be outstanding chalcogen bond (ChB) and halogen bond (XB) donors to recognize halide anions. Moreover, the interactions are found to be remarkably efficient with short distances and high directionality. Theoretical calculations further validate the presence of a deep σ ‐hole on Se, Te, and I.